Der Schwanendreher: Paul Hindemith’s Viola Concerto and Its Early Music Influences - Leona VARVARICHI (Studia Universitatis Babeş-Bolyai. Musica)
It is well known that much of Hindemith’s work is significantly influenced by early music, and Hindemith’s compositional style is marked by his use of fugue, ostinato, choral, canon, variations, and cantus firmus techniques. Thus, Sonata No. 5 for viola from cycle op. 11 or the Sonata for viola op. 31 No. 4, but also the Concerto for viola and small orchestra "Der Schwanendreher" are eloquent examples. The first part of this study highlights the musical personality of Paul Hindemith in the socio-political and cultural context of the beginning of the 20th century along with some particularities of his compositional style. I emphasize his interest in and closeness to the music of the Medieval, Renaissance, and Baroque eras and the influence that these particularities had on Hindemith’s musical thinking and compositional style. The second part includes the analysis of the Concerto for viola and small orchestra "Der Schwanendreher" in which I have highlighted some of the elements taken from the style of the aforementioned eras that inspired him to compose this work.